Assessment of Trainers’ Knowledge about Pragmatic Language for Children with Autism Spectrum Disorder - Marwah Salih Muslim, Zaid W. Ajil (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pragmatic consider an important part of the conversation. Children with autism have delay in the early language milestones based on standardized language tests. Study aimed: To assess the level of trainers’ knowledge about pragmatic language for children with autism spectrum disorder, and to find out relationships between trainers’ knowledge and their demographic characteristics. Methodology: Using the pre-experimental design of the current study, for one group of 47 trainers working at the private Autism Centers in Baghdad, data was collected from January 8/ 2022 to February 13 /2022. Using non-probability samples (convenient samples), self-management technology in which trainers fill out the questionnaire form themselves was used in the data collection process; it was analyzed through descriptive and inference statistics. Conclusion: The study concluded that there was no significant or weak correlation between the trainer’s knowledge and socio-demographic characteristics. The knowledge of the trainers ranged from medium to high in various dialogues.